Levosimendan prevents doxorubicin-induced cardiotoxicity in time- and dose-dependent manner: implications for inotropy - Efentakis, P; Varela, A.; Chavdoula, E; Sigala, F; Sanoudou, D.; Tenta, R; Gioti, K; Kostomitsopoulos, N.; Papapetropoulos, A.; Tasouli, A; Farmakis, D.; Davos, C.H.; et al. (Cardiovasc ResCardiovasc ResCardiovasc Res, 2020)
AIMS: Levosimendan (LEVO) a clinically-used inodilator, exerts multifaceted cardioprotective effects. Case-studies indicate protection against doxorubicin (DXR)-induced cardiotoxicity, but this effect remains obscure. We investigated the effect and mechanism of different regimens of levosimendan on sub-chronic and chronic doxorubicin cardiotoxicity. METHODS AND RESULTS: Based on preliminary in vivo experiments, rats serving as a sub-chronic model of doxorubicin-cardiotoxicity and were divided into: Control (N/S-0.9%), DXR (18 mg/kg-cumulative), DXR+LEVO (LEVO, 24 mug/kg-cumulative), and DXR+LEVO (acute) (LEVO, 24 mug/kg-bolus) for 14 days. Protein kinase-B (Akt), endothelial nitric oxide synthase (eNOS), and protein kinase-A and G (PKA/PKG) pathways emerged as contributors to the cardioprotection, converging onto phospholamban (PLN). To verify the contribution of PLN, phospholamban knockout (PLN-/-) mice were assigned to PLN-/-/Control (N/S-0.9%), PLN-/-/DXR (18 mg/kg), and PLN-/-/DXR+LEVO (ac) for 14 days. Furthermore, female breast cancer-bearing (BC) mice were divided into: Control (normal saline 0.9%, N/S 0.9%), DXR (18 mg/kg), LEVO, and DXR+LEVO (LEVO, 24 mug/kg-bolus) for 28 days. Echocardiography was performed in all protocols. To elucidate levosimendan's cardioprotective mechanism, primary cardiomyocytes were treated with doxorubicin or/and levosimendan and with N omega-nitro-L-arginine methyl ester (L-NAME), DT-2, and H-89 (eNOS, PKG, and PKA inhibitors, respectively); cardiomyocyte-toxicity was assessed. Single bolus administration of levosimendan abrogated DXR-induced cardiotoxicity and activated Akt/eNOS and cAMP-PKA/cGMP-PKG/PLN pathways but failed to exert cardioprotection in PLN-/- mice. Levosimendan's cardioprotection was also evident in the BC model. Finally, in vitro PKA inhibition abrogated levosimendan-mediated cardioprotection, indicating that its cardioprotection is cAMP-PKA dependent, while levosimendan preponderated over milrinone and dobutamine, by ameliorating calcium overload. CONCLUSION: Single dose levosimendan prevented doxorubicin cardiotoxicity through a cAMP-PKA-PLN pathway, highlighting the role of inotropy in doxorubicin cardiotoxicity.
Keywords: Animals; Antibiotics, Antineoplastic/*toxicity; Calcium Signaling; Calcium-Binding Proteins/genetics/metabolism; Cardiotoxicity; Cardiovascular Agents/*pharmacology; Cells, Cultured; control; Cyclic AMP-Dependent Protein Kinases/metabolism; Cyclic AMP/metabolism; Cyclic GMP-Dependent Protein Kinases/metabolism; Cyclic GMP/metabolism; Dose-Response Relationship, Drug; Doxorubicin/*toxicity; Female; Heart Diseases/chemically induced/metabolism/physiopathology/*prevention &; Male; Mammary Neoplasms, Experimental/*drug therapy/metabolism/pathology; Mice, 129 Strain; Mice, Inbred C57BL; Mice, Knockout; Myocardial Contraction/*drug effects; Myocytes, Cardiac/*drug effects/metabolism/pathology; Nitric Oxide Synthase Type III/metabolism; Proto-Oncogene Proteins c-akt/metabolism; Rats, Wistar; Simendan/*pharmacology; Time Factors